La dimension relationnelle de l'identité, composante essentielle du développement vocationnel féminin - Spain, Armelle; Hamel, Sylvie; Bédard, Lucille (Canadian Journal of Counselling and Psychotherapy, 2011)
Recent studies show the importance of the relational dimension in the professional lives of young women. Incidentally, there is not vet a theory of career development of women sufficiently coherent and clear that could encompass both the professional and the relational dimensions and eventually serve as basis for an intervention specifically directed towards assisting young women as they plan their future. This article presents the theoretical foundations of a research project aimed at developing such an intervention program. It is assumed that the integration of the relational and career dimensions will make more sense to girls and therefore increase their chances of entry and continuation on the job market.